Exergy analysis of the diesel pre-reforming solid oxide fuel cell system with anode off-gas recycling in the SchIBZ project. Part I: Modeling and validation. (23rd August 2018) - Valadez Huerta, Gerardo; Álvarez Jordán, Johanan; Dragon, Michael; Leites, Keno; Kabelac, Stephan
Abstract: Solid oxide fuel cell (SOFC) systems with anode off-gas recirculation (AGR) and diesel pre-reforming are advantageous because they can operate with the current fuel infrastructure. In the SchIBZ-project, the prototype of such a SOFC system for maritime applications has already been commissioned. In this first paper, we model the system devices to conduct an exergy analysis of this real SOFC plant and validate them with experimental values from experiments in laboratory scale. The results of our simulation agree well with the experimental values. The calculations with the validated results may be closer to the real thermodynamic behavior of such system components than previous literature. Highlights: The fuel cell system of the internationally well-known SchIBZ project is presented. The system is based on diesel fuel pre-reforming and anode off-gas recirculation. The diesel fuel model is based on experimental data. The fuel cell and reformer models were successfully validated with experiments in laboratory scale.